Maxillary Distraction Osteogenesis Using a Rigid External Distractor. Issue 4 (June 2015) - Kim, Jeenam; Uhm, Ki-il; Shin, Donghyeok; Lee, Jina; Choi, Hyungon
<x xml:space="preserve">Abstract</x> Introduction: Maxillary distraction osteogenesis is a reliable treatment for cleft lip and palate with midfacial retrusion. The purpose of this study was to evaluate the results of long-term follow-up in patients with cleft lip and palate after maxillary distraction osteogenesis and to find clinical factors related to relapse. From February 2002 to June 2008, 21 patients with severe class III malocclusion were treated at our hospital. We performed distraction osteotomy with a rigid external distractor device. The distraction length was more than 15 mm in all patients. Methods: Preoperative and postoperative lateral cephalometric radiographs were used for analysis. The sella-nasion-subnasale, sella-nasion-supramentale, and point-A-point-B-nasion (sella-nasion-subnasale–sella-nasion-supramentale) angles were recorded. The timelines for follow-up were preoperatively, after distraction, after consolidation, at 3 years, and once fully grown (5- to 8-year follow-ups). A comparative analysis of clinical factors was performed for the relapsing and nonrelapsing groups. Results: Of the 21 patients, 14 had relapsed. The mean age in the relapsing group was 9.1 years (7 boys and 7 girls) with 9 patients with unilateral cleft palate and 5 c bilateral cleft palate. The mean age in the nonrelapsing group was 11.7 years (4 boys and 3 girls) with 5 patients with unilateral cleft palate and 2 patients with bilateral cleft palate. Discussion: Despite greater anterior overcorrection, relapse occurred owing to scar tissue retraction and mandibular compensatory hypertrophy. The results suggest that the younger the patient, the more likely relapse will occur.